Moderasi Beragama: Perkokoh Persatuan dan Kesatuan Bangsa - Muthoharoh, Miftakhul (Proceedings of Annual Conference for Muslim Scholars, 2023)
Abstract: The diversity of the Indonesian nation is a necessity that cannot be avoided; the diversity of ethnicities, cultures and religious differences is unique to the Indonesian nation; however, with the existence of differences, conflict and friction are things that are inevitable in this nation, because That understanding of religious moderation to strengthen the nation is an absolute thing for the government to do as an effort to maintain the unity of this nation. The purpose of this writing is to discuss the concept of religious moderation in strengthening national unity; the method used is a literature review; this study concludes that it is needed to understand the values of religious moderation, namely being middle, not extreme, perpendicular, tolerance, deliberation, pioneering, improvement, love of the country, anti-corruption, respect for culture at all levels of society so that harmonization of national and national life can be achieved. Support is needed from the government, religious leaders, and educational institutions to socialize and develop religious moderation in society so that peace and harmony can be realized in living life